Firm Size, Profitability, and ESG Disclosure in Indonesia: Geographical Location As Moderating Variable - Risal Risal; Giriati Giriati; Wendy Wendy; Helma Malini (Yayasan Riset dan Pengembangan Intelektual, 2023)
Environmental, Social, and Governance (ESG) is a framework used to evaluate company performance on environment, social, and governance aspects. ESG disclosure is a means of communication used by companies to strengthen corporate legitimacy. This study aims to examine the effect of company size and profitability on ESG disclosure as moderated by geographical location, while also adding company age and leverage as control variables. This research employs a quantitative approach with purposive sampling technique. Data analysis uses moderating regression analysis (MRA). The results show that company size has no effect on ESG disclosure, while profitability has a significantly negative effect. Meanwhile, geographical location fails to moderate the effect of company size on ESG disclosure and geographical location significantly and negatively moderates the effect of profitability on ESG disclosure. The research contribution is that the ESG company level in each region indicates that external pressure and existing regulations have not been able to create significant differences between regions and this research also provides information to management, investors and stakeholders that geographical location is a company challenge and together to be able to pay attention to policies and decisions that can be made.